Identifikasi Ketebalan Lapisan Sedimen Menggunakan Data Mikrotremor Di Kecamatan Kadia Kota Kendari - La Hamimu Hamimu; Agnes Maindan; Abdul Manan (Program Studi Teknik Geofisika FITK UHO, 2023)
This study aims to determine the value of the distribution of sediment layer thickness. This research was conducted in the Kadia District area, Kendari City, with data collection carried out at 16 measurement points with intervals for each point varying from 400 to 600 meters with a sampling frequency of 100 Hz. The data obtained from this study is in the form of ground vibration data which is then downloaded software DataPro.exe East-Westhorizontal component, the North-South vertical component Up-Down. The downloaded microtremor data is then processed using a device software Geopsy 4.3.2 to obtain the H/V curve. The dominant frequency value (f0) is obtained from the H/V curve with a dominant frequency range of 1.247 Hz to 4.955 Hz and the shear (VS30) is obtained from the website www.USGS.gov with a VS30 of 276 m/s up to 301 m/s. Based on the data that has been obtained, the distribution value of the sediment layer thickness (h) will be determined. The value of the thickness of the sediment layer (h) in the study area ranged from 13,016 meters to 59,473 meters.